The influence of physical exercise on achievement motivation among college students: the mediating roles of self-efficacy and life satisfaction - Cao, Longan; Yu, Qianhang; Feng, Xin; Wang, Lei; Lang, Jun (Frontiers in Psychology, 2025)
BackgroundAs an inherent cognitive process in the pursuit of progress among college students, achievement motivation has become an indispensable facet of daily life. This study aims to investigate the association between physical exercise and achievement motivation, while also examining the mediating roles played by self-efficacy and life satisfaction.MethodsThis study employed a cross-sectional survey methodology, with a sample of 900 Chinese university students as the research participants. A total of 844 valid questionnaires were collected and analyzed. The participants completed various scales, including measures of sports activity level, self-efficacy, life satisfaction, and achievement motivation. Subsequently, comprehensive descriptive statistical analyses were conducted on the gathered data.Results and conclusionA significant positive correlation is present between physical exercise and achievement motivation (r = 0.464, p < 0.01), self-efficacy (r = 0.288, p < 0.01), and life satisfaction (r = 0.333, p < 0.01) among college students. Moreover, achievement motivation demonstrates a positive association with self-efficacy (r = 0.506, p < 0.01) and life satisfaction (r = 0.399, p < 0.01). Furthermore, the relationship between physical exercise and achievement motivation can be influenced by both self-efficacy and life satisfaction as mediators in our constructed mediation model where the total effect is 0.512 with direct effect of 0.348 and indirect effect of 0.163. The results of the constructed mediating effect model demonstrate that self-efficacy and life satisfaction serve as significant mediators and moderators, effectively enhancing the achievement motivation levels of college students. This study provides novel insights for enhancing intervention strategies to improve levels of achievement motivation not only among Chinese but also global college students.